Global, regional, and national burden of chronic kidney disease attributable to red meat consumption from 1990 to 2021 - Gu, Jie; Zhang, Jiaying (Frontiers in Nutrition, 2025)
ObjectivesHigh red meat is a crucial risk factor for chronic kidney disease (CKD). However, detailed reports on the burden of CKD due to red meat are limited. We aimed to assess the global, regional and national trends in CKD attributable to high red meat.Study designA comprehensive analysis was performed using data from the Global Burden of Diseases (GBD) 2021.MethodsAge-standardized mortality rates (ASMR) and age-standardized DALYs rates (ASDR) were key parameters used to evaluate CKD burden. The estimated annual percentage change (EAPC) was calculated to evaluate the secular trends of ASMR/ASDR. We further explored the associations of socio-demographic index (SDI) with ASMR/ASDR.ResultsFrom 1990 to 2021, CKD caused by high red meat led to a continuous rise in global ASMR/ASDR. Regionally, both ASMR and ASDR of CKD showed slight positive correlations with SDI, with correlation coefficients of 0.16 and 0.20, respectively. High SDI region experienced the heaviest disease burden, with the most significant increase in ASMR [EAPC 0.44 (95% CI: 0.36–0.52)], related to aging and epidemiological changes. Middle SDI region followed closely, with the highest ASDR increase [EAPC 0.44 (95% CI: 0.36–0.52)]. The USA had the highest number of CKD deaths due to high red meat, followed by China. Type 2 diabetes was the primary mediator linking increased red meat consumption to CKD.ConclusionCKD attributable to high red meat consumption has led to a continuous rise in global burden from 1990 to 2021, with high and middle SDI regions bearing the brunt of the burden.